Phase II study of a triple combination of oral vinorelbine, capecitabine and trastuzumab as first-line treatment in HER2-positive metastatic breast cancer - Chan, Arlene; Conte, P.; Petruzelka, L.; Tubiana-Mathieu, N.; Ganju, V.; Llombart, A.; Espie, M.; Majois, F.; Gil, M.; Vaissiere, N.; Villanova, G. (2013)
Chemotherapy plus trastuzumab is the standard first-line treatment for Human Epidermal Receptor 2-positive (HER2-positive) metastatic breast cancer. The aim of this international phase II trial was to determine the efficacy and safety profile of an oral chemotherapy doublet, oral vinorelbine plus capecitabine, and trastuzumab in this setting. Patients and Methods: In this single-Arm, multicenter, openlabel phase II study, in the first-line metastatic setting, patients received 3-weekly cycles of oral vinorelbine at 80 mg/m2 (first cycle dose 60 mg/m2) day 1 and day 8, plus capecitabine at 1000 (750 if =65 years) mg/m2 twice daily on days 1-14, plus trastuzumab at 4 mg/kg intravenously (i.v.) on day 1 (loading dose) then 2 mg/kg i.v. weekly thereafter. Treatment was continued until progression or unacceptable toxicity. Results: Fifty patients with a median age of 53.5 years were enrolled. Most (82%) had visceral involvement and 34% had more than two metastatic sites. The objective response rate (RECIST 1.0) in 44 evaluable patients was 77% [95% Confidence Interval (CI)=62-89%], including complete response in 21%. The clinical benefit rate (response or stable disease for =6 months) was 93% [95% CI=81-99%]. Median duration of response was 13.3 [95% CI=9.8-15.7] months, median progression-free survival was 12.8 [95% CI=10.8- 16.9] months and median overall survival was 47.0 [95% CI=30.5-64.3] months. Median number of cycles was 10 (range 1-81). The majority of patients (72%) received more than 18 weeks and 32% more than 48 weeks of treatment. The most frequent treatment-related grade 3/4 adverse events were neutropenia (71%), hand-foot syndrome (20%) and diarrhea (16%). A low-rate of grade 2 alopecia was observed (14%). Conclusion: The triple combination of oral vinorelbine, capecitabine and trastuzumab is highly active in terms of response rate, progression-free survival and overall survival, with a manageable toxicity profile.